If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = 15x + -100 + 50x + -25 Reorder the terms: 3 + x = 15x + -100 + 50x + -25 Reorder the terms: 3 + x = -100 + -25 + 15x + 50x Combine like terms: -100 + -25 = -125 3 + x = -125 + 15x + 50x Combine like terms: 15x + 50x = 65x 3 + x = -125 + 65x Solving 3 + x = -125 + 65x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-65x' to each side of the equation. 3 + x + -65x = -125 + 65x + -65x Combine like terms: x + -65x = -64x 3 + -64x = -125 + 65x + -65x Combine like terms: 65x + -65x = 0 3 + -64x = -125 + 0 3 + -64x = -125 Add '-3' to each side of the equation. 3 + -3 + -64x = -125 + -3 Combine like terms: 3 + -3 = 0 0 + -64x = -125 + -3 -64x = -125 + -3 Combine like terms: -125 + -3 = -128 -64x = -128 Divide each side by '-64'. x = 2 Simplifying x = 2
| 4/1 | | 3+3x+1-x=9 | | 6x^2+29x=-28 | | -5x+3(2x+11)=44 | | -3(2-y)-(7y+16)=-4(y-11) | | 16u^2-32u=9 | | 7x+8=7x-10 | | f(x)=x^3+7x^2+11x-3 | | 3+x=y | | 3+x/3=18 | | 20/1 | | (8x^3-7x^2+6x)+(3x^3+9x^2-14x)= | | m^2-8m+15=0 | | 29-(x+5)=7x-8 | | 2/3(x-4)+2=8 | | 3+x+3+x=3x | | 59-8x=-4x-29 | | (4-2)+3= | | 7x-8=7x+10 | | y=3/5x-3 | | (4+3)-2= | | (4*2)(3)= | | 3/5t-2=7 | | (2+4)(3)= | | 5x-10y=80 | | 42x^2+22x=4 | | X^2+14=-5 | | -164=5x+7(3x+10) | | 5/2c-8=-3 | | 6x-2(x-3)=10 | | -3(8-2a)+6(a-5)=-a+4(3-a) | | 2x+2(3x-7)=-78 |